Pengaruh People, Process dan Physical Evidence Terhadap Keputusan Mahasiswa Memilih STIBANKS Al Ma’soem (Tahun Akademik 2017/2018) - Rakhman, Faisal (Jurnal Riset Bisnis dan Investasi, 2018)
This research aimed to analyze the influence of People, Process and Physical evidence on the students' decision choice STIBANKS Al Ma’soem. This research uses quantitative associative method. The research data was obtained from primary data by distributing questionnaires to students in STIBANKS Al Ma'soem and then processed with IBM SPSS Statistic 23. The results showed that correlation is weak and there are not significant People, Process and Physical evidence on the students' decision choice STIBANKS Al Ma’soem. F test results showed that the factors of People, Process and Physical evidence does not significantly affect the students' decision choice STIBANKS Al Ma’soem. The R-square value obtained amounted to 0.1615, or 16.15%, that meaning simultaneous People, Process and Physical evidence contributes 16.15% to the effect on the students choice STIBANKS Al Ma’soem, and while the rest (1-R²) of 83.85% is the number of contributions made by other factors not examined. The study reveals that students expect fast response from the officer while giving information to students, such as academic information. Students also expect a simple procedure in order for their needs, such as to make academic letters. The management of STIBANKS Al Ma’soem must improve on other factors that can increase the number of students in the next period, such as service quality and promotion mix.